Assessing the research performance of Petrobras’ programs on research, development, and innovation (RD&I) - Marcos Eduardo Melo dos Santos; Patrícia Pereira da Silva; Hirdan Costa; Edmilson Moutinho dos Santos (Energy Strategy Reviews, 2023)
This paper assesses the existence of a relationship between recent research on the Research, Development, and Innovation (RD&I or R&D) sector of Petrobras with the quantitative data available in the company's reports and the Brazilian regulatory agencies. For this, 44 articles were selected using two main criteria: addressing the RD&I subject and being published in indexed peer-reviewed journals between 2000 and 2022. There are three perspectives from which the company RD&I (state development, human resources, and innovation clusters), increase in patents and production, and cost reduction are directly related to the qualitative and quantitative variation of innovation networks, state policies, and the improvement of internal human resource policies. Additionally, it was discovered that short-term outcomes could not be correlated with the level of training or R&D spending. However, a long-term drop in investment could lead to hazards such a decline in researchers, technical advancement, oil reserves, and the rate of output growth.